Tax Morale and Public Sector Revenues in Baltic Countries - Rutkauskas, Virgilijus (Socialinė teorija, empirija, politika ir praktika, 2019)
This article investigates issues behind households’ tax payment morale, theoretical and practical aspects of the tax payment gap, and its impact on public sector revenue in Baltic countries. The attitude of households on tax payment is assessed quantitatively by employing a dichotomous logit-probit regression analysis. The tax payment gap among Baltic households has been investigated by applying a “macro approach,” the main components of which are the shadow economy and the total tax rate. The effect of any hypothetical changes in tax morale is assessed by applying social accounting matrixes, which are based on national account data and allow to keep the economy balanced at all time. The results presented in this research suggest that taxes uncollected from households constitute nearly one fifth of total general government revenues and count nearly one tenth of the nominal GDP. Measures applied to strengthening tax morale positively contribute to public sector revenue and in general to the economy, though they should be applied gradually.
Keywords: tax payment gap; tax morale; public sector revenue; logit-probit analysis; social accounting matrixes